DEVELOPMENT AND EXPERIMENTAL STUDY OF HYPOGLYCEMIC COMPOSITION PREPARED FROM MEDICINAL PLANTS - A. M. Kutovaya; I. A. Martinchik; T. E. Trumpe; E. V. Ferubko; V. N. Davydova (Разработка и регистрация лекарственных средств, 2019)
Experimental study of the hypoglycemic properties of composition, prepared from medicinal plants has showed in terms of glucose tolerance test. There increases in animals by loading of glucose the tolerance to carbohydrates. The conclusion about the prospects of further pharmacological study of the original composition prepared from medicinal plants is positive with the aim of developing the antidiabetic agents.